2017
DOI: 10.1177/0022022117746239
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Timing in Reciprocity: An Investigation of Reciprocity Norms Among Indians and Americans

Abstract: After receiving help, individuals tend to experience an immediate increase in obligation to be responsive to the helper. Cross-cultural research has shown that whereas this sense of obligation dissipates for Americans after reciprocation, it remains unchanged after reciprocation for Indians. Is this decrease in obligation felt by Americans temporary, or can it endure over years such that it provides immunity from responding to the helper? And is there a statute of limitations on the experience of obligation fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…The goal of this pilot study was to establish that Americans and Indians hold contrasting normative standards and understandings of reciprocity (thereby replicating past findings on cultural differences in reciprocity norms; Goyal & Miller, 2018; Miller et al, 2017, 2014; Wice et al, 2018). The pilot study involved a story completion task that tapped both the contrasting expected behavior about giving gifts in a social exchange and the contrasting meanings associated with giving gifts after receiving help held by Indian and American participants.…”
Section: Pilot 1: Pilot Study On Reciprocity Normsmentioning
confidence: 73%
See 1 more Smart Citation
“…The goal of this pilot study was to establish that Americans and Indians hold contrasting normative standards and understandings of reciprocity (thereby replicating past findings on cultural differences in reciprocity norms; Goyal & Miller, 2018; Miller et al, 2017, 2014; Wice et al, 2018). The pilot study involved a story completion task that tapped both the contrasting expected behavior about giving gifts in a social exchange and the contrasting meanings associated with giving gifts after receiving help held by Indian and American participants.…”
Section: Pilot 1: Pilot Study On Reciprocity Normsmentioning
confidence: 73%
“…The choice of these two domains was deliberate, as Americans and Indians rely on different norms and hold different interpretations of the same behavior in these domains. It is normative among Americans (but not Indians) to give gifts after receiving help from a friend and these gifts are interpreted as reciprocal actions (Goyal & Miller, 2018; Miller, Akiyama, & Kapadia, 2017; Miller et al, 2014). Likewise, it is normative among Indians (but not Americans) to avoid shoes coming into contact with sacred objects (such as books) and if they do it is interpreted as spiritually contaminating (Shweder, Mahapatra, & Miller, 1987; Shweder, Much, Mahapatra, & Park, 1997).…”
Section: Culture Expertise and Meaning-makingmentioning
confidence: 99%
“…However, in the case of communal norms, individuals balance inputs and returns over extended periods of time (Clark & Aragón, 2013). In a recent study using psychological experiments, Goyal and Miller (2018) observed that Indians (in comparison with American counterparts) are less likely to experience a reduction in obligation for maintaining reciprocity.…”
Section: Len-denmentioning
confidence: 99%
“…In a three-study cross-cultural investigation, we demonstrated that Indians relied more frequently on communal norms in helping friends whereas Americans relied more frequently on reciprocal exchange (Miller et al, 2014). This was seen in Indians reciprocating by being responsive to the friend’s needs when and if such needs arose, even years into the future, and Americans reciprocating through expressive gestures given soon after receiving help, such as by sending flowers (see also Goyal & Miller, 2017). We provided direct evidence that Americans were motivated by exchange and not solely by gratitude or by politeness norms in a follow-up vignette-based experiment demonstrating that only Americans and not Indians were less inclined to help a friend who had helped them if they had already reciprocated by taking the friend out for dinner (and thus had at least partially repaid their debt) than if they had not reciprocated (and thus were still fully in debt).…”
Section: Cultural Variability In Norms Of Reciprocitymentioning
confidence: 99%